2011
DOI: 10.1007/s10126-011-9369-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity, Chemical Profiling, and 16S rRNA-Based Phylogeny of Pseudoalteromonas Strains Collected on a Global Research Cruise

Abstract: 1One hundred one antibacterial Pseudoalteromonas strains that inhibited growth of a Vibrio 2 anguillarum test strain were collected on a global research cruise (Galathea 3), and 51 of the strains 3 repeatedly demonstrated antibacterial activity. Here, we profile secondary metabolites of these 4 strains to determine if particular compounds serve as strain or species markers and to determine if 5 the secondary metabolite profile of one strain represents the bioactivity of the entire species. 16S 6 rRNA gene simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
92
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 60 publications
8
92
1
Order By: Relevance
“…In addition, the isolates belonging to the most commonly recovered genera, Pseudoalteromonas and Psychrobacter, were retrieved from almost all the samples tested, showing their ubiquitous distribution in the coastal ecosystems of Potter Cove. These results agree with those reported by other authors who have isolated several species of these genera from many Antarctic environments (Bozal et al 1997;Bowman 1998;Bozal et al 2003;Vynne et al 2011). Among the isolates obtained in each Antarctic expedition, we found enzyme producers in all groups except NR, in which all isolates were obtained from the fish Notothenia rossi.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the isolates belonging to the most commonly recovered genera, Pseudoalteromonas and Psychrobacter, were retrieved from almost all the samples tested, showing their ubiquitous distribution in the coastal ecosystems of Potter Cove. These results agree with those reported by other authors who have isolated several species of these genera from many Antarctic environments (Bozal et al 1997;Bowman 1998;Bozal et al 2003;Vynne et al 2011). Among the isolates obtained in each Antarctic expedition, we found enzyme producers in all groups except NR, in which all isolates were obtained from the fish Notothenia rossi.…”
Section: Discussionsupporting
confidence: 92%
“…Some bacterial strains isolated from seawater inhibited the growth of marine and human pathogens (Table 1; Gram et al 2010;Bernbom et al 2011;Vynne et al 2011). The highest antibacterial activity was observed among Pseudoalteromonas and Ruegeria isolates.…”
Section: Antibacterial Activity Heterotrophic Bacteriamentioning
confidence: 99%
“…For example, a strain of B. licheniformis lost its bioactivity when it was cultured in a liquid medium instead of on agar surfaces (Yan & Boyd 2002;Matz et al 2008). Similarly, Pseudoalteromonas isolates attached to biotic or abiotic surfaces are more likely to have antibacterial properties than planktonic isolates (Vynne et al 2011). Mucus of the coral Acropora palmata inhibited antibiotic and pigment production by the 'visitor' isolate Pseudoalteromonas sp.…”
Section: Antibacterial Activity Heterotrophic Bacteriamentioning
confidence: 99%
“…Similarly, Grossart et al (38) found that the production of antibiotic by a biofilm community did not affect newcomers to the biofilm. Of the four Pseudoalteromonas species in the present study, three (P. piscicida, P. tunicata, and P. ulvae) represent the pigmented, antibiotic-producing subgroup, whereas P. antarctica, despite a brownish colony color, represents the nonpigmented, non-antibiotic-producing cluster (46,47). In the simple (sterile seawater) systems, we observed no consistent difference in repelling or attracting characteristics between P. antarctica and the pigmented strains, further supporting the above-mentioned studies that could not correlate antibiotic production to a subsequent repelling effect (38,45).…”
Section: Discussionmentioning
confidence: 77%
“…A high-M w protein has been identified as an antibacterial compound (48), and an alkaloid (norharman) was identified as a cytotoxic compound (49). P. piscicida also produces brominated peptides (46,47) that have a cytotoxic effect (50). Despite several attempts, we have not been able to purify the antibacterial compound(s).…”
Section: Discussionmentioning
confidence: 99%